Morphogenetic and structural comparative characterization of tropical forage grass cultivars under free growth Caracterização morfogênica e estrutural comparativa de cultivares de gramíneas forrageiras tropicais sob crescimento livre - da Silveira M.C.T. (2010)
Understanding of the morphogenetic characteristics allows comprehension of aspects related to the form and function of forage plants, providing opportunities to identify potentially high productive plants and distinct defoliation management requirements. The objective of this experiment was to carry out a comparative study of ten tropical forage grasses using morphogenetic and structural variables. Treatments corresponded to grasses of the Panicum genus (P. maximum cultivars Tanzânia and Mombaça) and the Brachiaria genus (B. brizantha cultivars Piatã, Marandu, Xaraés, Capiporã and Arapoty; B. decumbens cultivar Basilisk; B. humidicola cultivars Comum and Tupi), evaluated under free growth conditions. Response variables were leaf appearance and elongation rates, phyllochron, stem elongation rate, final leaf length, number of live leaves per tiller, leaf life span and tiller appearance, death and survival rates. There was difference between cultivars for these variables, indicating a large variability within plants. Considering the morphogenetic and structural variables of leaves and tillers, B. brizantha had a similar pattern of variation to those of P. maximum, and B. Decumbens, similar to those of B. humidicola. Tiller appearance was large at the onset of the experiment and second and third generations comprised the large majority of tiller population for the cultivars Mombaça, Tanzânia, Xaraés and Capiporã. Group analysis based on plant morphogenetic and structural characteristics of leaves and tillers was an interesting way of grouping cultivars, indicating the importance and the potential of using morphogenesis in plant selection and evaluation programmes.